The impact of salesperson’s training on organizational outcomes - Rahman, M. Khalilur; Zailani, Suhaiza; Mamun, Abdullah Al; Jan, Muhammad Tahir; Amerziane, Alileche; Hazeez, Abdulsalam (JSRAD, 2015)
Quality of human resource is an asset to organization. Consequently, quality training can promote both personal and organizational success. This study suggests that training on salesperson’s knowledge and skills can develop the positive beliefs and attitudes which lead to enhance organizational outcomes. Most organizations meet their needs for training in a haphazard way rather than design training in a rational way. The aim of the study is intended to investigate the impact of training on salespeople’s knowledge and skills for organizational benefits. Data were gathered by surveying 238 salespeople in the Malaysian major retail shopping malls. Data were analyzed using the partial least square technique. Training has significant impact on salesperson’s experience (salesperson’s knowledge and salesperson’s skills), while salesperson’s experience has positive impact on the three categories of organizational outcomes (i.e., productivity, effectiveness and perfor